Pengaruh Iklan Media Sosial Instagram terhadap Minat Beli Masyarakat Pada E-Commerce - Alya Elita Sijoen; Maasyithah Hutagalung; Evi Sirait; Siska Armawati Sufa; Musran Munizu (Jurnal Informatika Ekonomi Bisnis, 2024)
This research aims to examine the influence of advertising and Instagram social media on people's buying interest in e-commerce. Sampling was carried out using purposive sampling technique. This research uses multiple linear regression analysis techniques with SPSS as an analysis tool. Based on the results of data testing carried out, it shows that advertising partially has a significant effect on people's buying interest in e-commerce, Instagram social media has a significant effect on people's buying interest in e-commerce.